The Effect of Illumination Intensity on the Performance of Germanium Based-Thermophotovoltaic Cell - Gamel M.M.A.; Jern K.P.; Rashid W.E.; Yau L.K.; Jamaludin M.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Conversion efficiency; Cost effectiveness; Cytology; Efficiency; Electronic design automation; Germanium; Infrared radiation; Nanoelectronics; Atmospheric perturbations; Cell conversion efficiency; Electrical performance; Illumination conditions; Light intensity; Silvaco; Thermophoto voltaic cells; Thermophotovoltaic systems; Cells